The expert in litigation and arbitration - Cato, D. Mark. (London : LLP, 1999)
The book expert in litigation and arbitration explore ways of making the introduction of expert evidence in arbitration and litigation more cost effective. This book aims to display humility and commonsense as well as expertise and is all the better for that.
Includes index.
Include bibliography ,reference and index
ocf, 17/04/19
Loans
Keywords: Litigation; Arbitration